2017
DOI: 10.4172/2161-0959.1000301
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A Detection by HPLC-FL in Processed Baby Foods

Abstract: Abstract270 samples of different types of pasta and cereal products, distributed in a nursery school canteen in Milan (Italy), were analyzed to estimate the occurrence of ochratoxin A.OTA was found in all analyzed samples (100%), 39 samples exceeded the maximum limit established by European Commission Regulation for OTA in the foodstuffs listed in the relevant category.The mean concentration of ochratoxin A in samples of pasta, intended for children (over 5 months) consumption was 0.56 µg/kg; the mean concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Although studies have shown that the processing of food can lead to a reduction or degradation of mycotoxins, it is important to highlight that mycotoxins can be carried over to the final processed products, thus necessitating the need for good quality raw material [56][57][58]. Available studies in the world have revealed the occurrence of both regulated and non-regulated mycotoxins in foods for IYC, including the so-called "emerging mycotoxins" [59][60][61][62][63][64][65][66][67][68][69][70][71]. In SSA, only a few studies have focused on food products for infants and children.…”
Section: Cereal-based Productsmentioning
confidence: 99%
“…Although studies have shown that the processing of food can lead to a reduction or degradation of mycotoxins, it is important to highlight that mycotoxins can be carried over to the final processed products, thus necessitating the need for good quality raw material [56][57][58]. Available studies in the world have revealed the occurrence of both regulated and non-regulated mycotoxins in foods for IYC, including the so-called "emerging mycotoxins" [59][60][61][62][63][64][65][66][67][68][69][70][71]. In SSA, only a few studies have focused on food products for infants and children.…”
Section: Cereal-based Productsmentioning
confidence: 99%